Bacterial transport in porous media - Teo, Ting Wei (Nanyang Technological University, 2022)
Bacteria are ubiquitous in our environment and play important roles in our ecosystem. The process of bacterial transportation often leads to modifications of the natural porous environment through phenomena such as biofilm formation and causes a reduction of permeability. It has been observed in various researches that bacterial cells are able to travel through large distance across a porous medium. The ability of bacterial cells travelling through large distance allows them to get deposited and attached onto surfaces, potentially increases the chances to start the cycle of biofilm formation, where planktonic cells can aggregate and secretes extracellular polymeric substance and releasing new planktonic cells into the environment and rapidly colonize the environment. While there is a vast research exploring the effects of bacterial biofilm on the alteration of permeability of the porous medium, little attention is given to the deposition of individual bacterial cells and the effects of distribution of porosity on the resultant spatial distribution of bacterial cells. The advent of lab-on-chip microfluidic technologies has enabled a myriad of new applications in biomedical, rapid sensing and detection of microorganism, and integration of multiple traditional laboratory procedures into an automated lab-on-a-chip system. Detection of bacteria by microfluidic systems has been demonstrated by means of electrochemical, nanoparticle based, and colorimetric detection, with significantly reduced footprint. Recently, a microfluidic platform “soil-on-a-chip” was coined to simulate complex soil environment and to investigate how organisms interact with soil environment. These soil-on-a-chip platforms offer precise spatiotemporal control on the microenvironments in terms of temperature, pH, gas composition, porosity and water saturation, which is essential for the understanding of soil organisms such as bacteria and fungi. Nonetheless, the effects of bacteria transport on the medium’s permeability, the dynamics such as the initiation and propagation of bacterial cells attaching onto the surfaces, preferential path and the mechanics of bacterial cells retention in the porous medium are yet to be fully explored. The quantification of the permeability of porous medium and the effects of bacteria contributing to the reduction of permeability may be investigated.